MarioHeart: Novel In-Vitro Flow Model for Testing Heart Valve Prostheses and Anticoagulant Therapies. Issue 5 (12th March 2023) - Devos, Maxime; Liesdek, Omayra C. D.; Suyker, Willem J. L.; van Tuijl, Sjoerd; Schutgens, Roger E. G.; van de Vosse, Frans N.; de Heer, Linda M.; Rutten, Marcel C. M.
Abstract : Mechanical heart valve (MHV) prostheses present a risk of thromboembolic complications despite antithrombotic therapy. Further steps in the development of more hemocompatible MHVs and new anticoagulants are impeded due to the lack of adequate in-vitro models. With the development of a novel in-vitro model (MarioHeart), a pulsatile flow similar to the arterial circulation is emulated. The MarioHeart design owns unique features as 1) a single MHV within a torus with low surface/volume ratio, 2) a closed loop system, and 3) a dedicated external control system driving the oscillating rotational motion of the torus. For verification purposes, a blood analog fluid seeded with particles was used to assess fluid velocity and flow rate using a speckle tracking method on high-speed video recordings of the rotating model. The flow rate resembled the physiological flow rate in the aortic root, in both shape and amplitude. Additional in-vitro runs with porcine blood showed thrombi on the MHV associated with the suture ring, which is similar to the in-vivo situation. MarioHeart is a simple design which induces well-defined fluid dynamics resulting in physiologically nonturbulent flow without stasis of the blood. MarioHeart seems suitable for testing the thrombogenicity of MHVs and the potential of new anticoagulants.